Fatigue and diabetes mellitus: a prospective study - Kaur, Parminder; Chugh, S. N.; Singh, Harpreet; Tanwar, Vikram S.; Sukhija, Gagandeep; Mathur, Rekha (International Journal of Advances in Medicine, 2019)
Background: Fatigue is a common complaint among patients with diabetes mellitus (DM) that can undermine the daily functional activities of a person. The objectives of the study were to assess the fatigue in patients of newly diagnosed type 2 DM and to relate fatigue with blood glucose parameters (BGP) and glycemic control. Methods: A total 50 patients of type 2 DM, diagnosed as per American Diabetes Association 2011 criteria, were enrolled in the study group. Each subject was evaluated two times for fatigue using Multidimensional Fatigue Symptom Inventory-Short Form (MFSI-SF) scale. 1st assessment was at the time of enrollment and 2nd was done after achieving target control of type 2 DM. Values of Fasting blood glucose (FBG), postprandial blood glucose (PPBG), blood glucose variability (BGV) and glycosylated hemoglobin (HbA1c) were obtained for each subject at each assessment. Data collected was analyzed statistically. Results: Mean age of study group was 50.7±8.9 years with male to female ratio of 1.17:1. Mean values of MFSI-SF score at 1st and 2nd assessment were 14.10±17.97 and 4.64±14.06, respectively indicating a statistically significant improvement in fatigue (p<0.05) after achieving target control. Overall fatigue, general fatigue, emotional fatigue, and vigor score correlated significantly with glycemic control (HbA1c) with correlation coefficient (r) of 0.337, 0.351, 0 .339, and - 0.281, respectively (all p <0.05). Conclusions: Fatigue had a positive correlation with FBG, PPBG and BGV and HbA1c. A significant improvement in all the parameters of fatigue was noted after control of diabetic status.